Comparison of AIA and FIDIC Construction Contracts with an equivalent Egyptian contract - Khaled Al Bayomi; Tamer Elkorany; Adel Eldosouky (Journal of Engineering Research - Egypt)
Precisely drafting the infrastructure construction contract is a way to ensure the success and continuity of the project without any complications, and through which the rights and duties of each party involved in the project are determined. International standard contract conditions such as FIDIC and AIA contribute significantly to reducing disputes between the parties; yet, due to the absence of a standard construction contract in Egypt, the infrastructure construction industry became more complicated in recent years and contractual commitments are often not carried out in a good faith. This research aims to highlight the major causes of contractual conflicts that may be addressed in infrastructure construction projects and to compare and analyze the Egyptian Construction Contract (ECC), International Federation of Consulting Engineers (FIDIC), and American Institute of Architects (AIA) construction contracts for the clauses that cause disputes in the Egyptian infrastructure construction contract in order to improve, develop, and enhance the ECC as well as overcome the obstacles that hinder the development of infrastructure construction projects, leading to an increase in the chances of achieving basic project success indicators (cost, time, quality, and safety).